Pengaruh Electronic Word of Mouth (E-Wom) di Instagram terhadap Destination Image di Farmhouse Susu Lembang, Bandung - Miftakhul Noviyanti; Nungky Puspita; Riza Firmansyah (Fakultas Pariwisata Universitas Pancasila, 2018)
Following the growth and evolution of the internet, electronic word of mouth have become an important phenomenon. The objective of this research is to analyze how the effect of electronic word of mouth (eWOM) in social media instagram toward destination image. This research applied quantitative approach. The sample of this research is 100 respondent who knew about Farmhouse Susu Lembang instagram account, collected using non-probability sampling. This research used questionnaire as research instrument and analyzed with multiple regression. The result of this research that the dimensions of negative feelings venting, concern for others, social benefits, and advice seeking from eWOM variables have significant influence, and the dimensions of platform assistance, expressing positive feelings, economic incentives, and helping the company from variables electronic word of mouth (eWOM) on Instagram social media has no significant effect on destination image.